ABOUT EDUCATION IN THE INFORMATION AGE - Xusanov Axmadjon Jurayevich; Auchynnikau Yauheni (Galaxy International Interdisciplinary Research Journal, 2023)
Rapidly developing information communication technologies are bringing significant changes to all aspects of our daily lives. Currently, the concept of "information" is frequently found as a special "brand" sign that can be purchased, sold, exchanged for some other "brand". Today, the view that a person who owns information, can search, create, analyze, and distribute information also owns the world has been elevated to the level of truth. (Matthew 24:14; 28:19, 20) Therefore, it is important to prove that our young people are no less than anyone else among their foreign peers, to work equally among equals, and to develop the ability to make full use of information and communication technologies in the educational process so that our future becomes a truly decisive force.